Odpowiedzi

Najlepsza Odpowiedź!
2010-02-27T14:18:46+01:00
Naoh + hcl -> nacl + h2o
2naoh + h2s -> na2S +2 h2o
naoh + hno3 -> nano3 + h2o
2naoh + h2co3 -. na2co3 +2 h2o
2naoh + h2so4 -> na2so4 + 2h2o
2naoh + h2so3 -> na2so3 + 2h2o
3naoh + h3po4 -> na3po4 + 3h2o

Z KOH tak samo tylko zamiast Na masz K

Ca(oh)2 +2hcl -> cacl2 + 2h2o
Ca(oh)2 + h2s -> caS + 2h2o
Ca(oh)2 + 2hno3 -> ca(no3)2 + 2h2o
Ca(oh)2 + h2co3 _> caco3 + 2h2o
3Ca(oh)2+ 2h3po4 -> ca3(po4)2 + 6h2o
Ca(oh)2 + h2so4 -> caso4 + 2h2o
Ca(oh)2 + h2so3 => caso3 + 2h2o

Z Mg(oh)3 tak samo tylko zamiast Ca wpisujesz Mg


1 5 1